Examining U.S. inflation across households grouped by equivalized income. (Monthly Labor Review, 2024)
This document provides a comprehensive analysis of inflation rates across different income groups in the United States. It highlights that lower income households generally face higher inflation rates compared to higher income households, with the inflation gap being larger when measured with the Chained Consumer Price Index. The document discusses the methodology used by the Bureau of Labor Statistics to calculate expenditure weights and price indexes, as well as the demographic characteristics and spending patterns of households in different income quintiles. It also presents a comparison of price changes for different expenditure categories based on spending shares of households in the lowest and highest income quintiles. The findings are based on data provided by the U.S. Bureau of Labor Statistics.